Penerapan Aplikasi Akuntansi SAKU Pada Laporan Keuangan UKM (Studi Kasus Pada Toko Arienas Motor) - Shofiana, Ana Putri; Damayanti, Damayanti (Jurnal Kompetitif Bisnis, 2022)
This study aims to identify the application of the SAKU accounting application to meet the needs of the Arienas Motor Store accounting information system. The results of this study are useful and provide information to SMEs so that they can be used as a reference for implementing the SAKU Accounting Application, thereby supporting SMEs in their record and financial reporting processes and increasing their profitability. Or allow profit to be determined. losses incurred by the company. This type of research uses a qualitative approach. Data collection was conducted through participant observation, interviews and documentation. Data were collected using targeted sampling techniques and data analysis was performed using triangulation. Based on the findings, it can be concluded that the use of the SAKU application in the Arienas Motor Store can help and support the operational activities of the store even if the store owner does not have sufficient knowledge of accounting increase. With the SAKU app, store owners can know the financial data of the store from profit and loss statements and trial balances. With SAKU’s accounting app, you can keep track of your monthly balance. The SAKU accounting application also minimizes input and calculation errors.